1996
DOI: 10.1097/00006123-199608000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Psychological Testing in Patients Undergoing Spinal Cord Stimulation: A Prospective Study

Abstract: Because our study population was selected on the basis of recognized prognostic factors and long clinical experience, it may not be possible to generalize our findings to the overall pain clinic referral population. In the subpopulation we have chosen for SCS trials, psychological testing is of modest value and explains little of the observed variance in outcome. We find little evidence for selecting patients for SCS on the basis of psychological testing. Because self-reported outcome measures may themselves r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 48 publications
2
71
0
4
Order By: Relevance
“…Not all patients are suitable for the PMP, and patients with unrealistic goals have been shown to have a poor outcome following PMP treatment. [42][43][44] These patients can be very difficult to manage and should be managed by conservative means by close collaboration between GPs and pain clinics, using containment strategies. Some patients can become suitable for PMP therapy with individual psychological and/or physiotherapy treatment sessions.…”
Section: Multidisciplinary Team Assessment and Patient Preparation Fomentioning
confidence: 99%
“…Not all patients are suitable for the PMP, and patients with unrealistic goals have been shown to have a poor outcome following PMP treatment. [42][43][44] These patients can be very difficult to manage and should be managed by conservative means by close collaboration between GPs and pain clinics, using containment strategies. Some patients can become suitable for PMP therapy with individual psychological and/or physiotherapy treatment sessions.…”
Section: Multidisciplinary Team Assessment and Patient Preparation Fomentioning
confidence: 99%
“…298,320 Most of this literature involves spinal cord stimulation; however, this information can be applied to long-term intraspinal drug delivery.…”
Section: Psychological Screeningmentioning
confidence: 99%
“…Few studies have examined the usefulness of prognostic factors [12,13], and these studies have not found good predictors of outcome. Clinical experience suggests, however, that some patients are poor candidates for stimulation.…”
Section: Discussionmentioning
confidence: 99%